Produktivitas Penangkapan Ikan Air Tawar Dengan Alat Tangkap Bubu Dasar di Sungai Tommo Kabupaten Mamuju - Irsandi, Irsandi; Kantun, Wayan; Demallulu, Arnold (Jurnal Riset Diwa Bahari (JRDB), 2025)
Bubu is a traditional fishing tool for catching freshwater fish in areas around rivers, lakes and swamps. Catches using traps tend to decrease. In connection with this, this research aims to analyze the productivity of traps using different baits. This research was conducted from May to June 2023 in Tommo Village, Mamuju Regency. This research is classified as a type of experimental research with the design used in this research being a Randomized Block Design with three groups and four different bait treatments, namely no bait, fine bran, corn and sweet potatoes. Determination of sampling stations was carried out by purposive sampling according to the conditions of the research site. The results showed that the composition of fish species caught with 287 bran baits, 41 sweet potato baits and 76 corn baits. Distribution of catch weight using bran bait 0.193 ± 0.140 g, sweet potato bait 0.167 ± 0.166 g and corn 0.209 ± 0.150 g. Productivity based on overall catch for bran, sweet potato and corn bait respectively 71.04; 10.15 and 18.81%. Based on the catch rate, the productivity obtained with bran bait was 1.844 g/trip, sweet potato bait 0.228 g/trip and corn bait 0.531 g/trip. The highest productivity by station was obtained by using bran feed at station III. The best productivity was using bran bait while the highest weight was using corn bait.